Online Shopping Behavior of Students in Ho Chi Minh City: A Case Study on TikTok Shop Livestreams - Khang, Nguyen Tan; Nguyen, Nga Thi Linh; Tran, Thu Ngoc Minh; Huynh, Huong Thi Thao; Tran, Nga Thi Hong; Nguyen, Kiet Tuan (Lembaga Penelitian & Pengabdian Masyarakat Universitas Bina Sarana Informatika, 2025)
This study analyzes the current state of online shopping through Livestreams on TikTok Shop among students in Ho Chi Minh City, with a case study focusing on students from the University of Social Sciences and Humanities Vietnam National University, Ho Chi Minh City. To achieve the research objectives, the authors combined quantitative methods with a systematic review, collecting data through convenience sampling, resulting in a total of 462 survey responses. Additionally, the study applies the Theory of Planned Behavior and the Uses and Gratifications Theory to examine factors influencing students’ online shopping behavior on TikTok Shop Livestreams. The findings indicate that factors such as promotions, psychology, technology, and social influence significantly impact students' shopping habits. Through this study, the authors provide new insights for marketers and e-commerce platforms to optimize their strategies while enhancing students' shopping experiences in the digital commerce environment